2017
DOI: 10.1900/rds.2017.14.295
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Deprivation, Household Education, and Employment are Associated With Increased Hospital Admissions and Poor Glycemic Control in Children With Type 1 Diabetes Mellitus

Abstract: Early intervention and education from primary care and specialist diabetes teams within the community in deprived areas may be effective in reducing hospital admissions for diabetes-related problems and improving glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Another explanation could be the higher proportion of families with low socioeconomic status in the eastern part of the country [30]; a recent study showed that children and adolescents from families with low soci-oeconomic status in Germany are hospitalized more frequently and longer than other children [31]. Moreover, there is some evidence that a higher regional deprivation in the eastern part of Germany leads to worse diabetes outcomes, and also to increased hospital admissions [10,32].…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation could be the higher proportion of families with low socioeconomic status in the eastern part of the country [30]; a recent study showed that children and adolescents from families with low soci-oeconomic status in Germany are hospitalized more frequently and longer than other children [31]. Moreover, there is some evidence that a higher regional deprivation in the eastern part of Germany leads to worse diabetes outcomes, and also to increased hospital admissions [10,32].…”
Section: Discussionmentioning
confidence: 99%
“…8 Social deprivation is a significant factor that affects glycaemic control, with poorer HbA 1c levels seen in those from more deprived areas. 9 Our results showed that children who were less likely to download their data were from more deprived areas with poorer income. This has implications for the resources, education and support that healthcare professionals should provide for the management of type 1 diabetes and the use of technology required for routine downloading of blood glucose data.…”
Section: T a B L E 1 Difference In Variables Between Routine And Non-mentioning
confidence: 60%
“…Social deprivation is a significant factor that affects glycaemic control, with poorer HbA 1c levels seen in those from more deprived areas 9 . Our results showed that children who were less likely to download their data were from more deprived areas with poorer income.…”
Section: Variable Routine Downloader (N = 33) Non Downloader (N = 65)mentioning
confidence: 67%
“…All paediatric inpatient and outpatient work is mainly based at Ormskirk District General Hospital. In terms of population health, Southport and Ormskirk, like many other parts of the UK, has seen a steady rise in younger children diagnosed with type 1 diabetes …”
Section: Southport and Ormskirk Hospital Nhs Trustmentioning
confidence: 99%